Human oncogenic herpesvirus latency proteins activate NEK2 to promote chromosomal instability and tumorigenesis - Dipayan Bose; Nian Ma; Rajnish Kumar Singh; Ramakrishna Vangala; Atharva Torne; Kiran Chunduru; Erle S. Robertson (Proceedings of the National Academy of Sciences, 2026)
Never in mitosis A (NIMA)-related kinase 2 (NEK2) is a serine/threonine kinase that plays a crucial role in cell cycle regulation and is frequently induced across multiple cancer types, where its elevated levels are associated with poor prognosis. Epstein–Barr virus (EBV) and Kaposi’s sarcoma–associated herpesvirus (KSHV), both known to drive various malignancies, were observed to induce NEK2 expression during both primary infection and latent phases of infection. Increased NEK2 expression contributes to chromosomal instability by promoting nondisjunction, leading to a rise in aneuploid cell populations and fostering uncontrolled cell proliferation. Mechanistically, EBV latent protein EBNA2 and KSHV latent antigen LANA were identified as principal regulators of NEK2 upregulation, acting through modulation of RBP-Jκ activities at the NEK2 promoter region. Additionally, we demonstrated that targeting NEK2 impaired EBV- and KSHV-mediated tumor progression, highlighting its potential as a critical driver of virus-induced oncogenesis and a promising therapeutic target.